Dual Effect of Acetic Acid Efficiently Enhances Sludge-Based Biochar to Recover Uranium From Aqueous Solution - Yu, Shoufu; Wu, Xiaoyan; Ye, Jian; Li, Mi; Zhang, Qiucai; Zhang, Xiaowen; Lv, Chunxue; Xie, Wenjie; Shi, Keyou; Liu, Yong (Frontiers in Chemistry, 2022)
Excess sludge (ES) treatment and that related to the uranium recovery from uranium-containing wastewater (UCW) are two hot topics in the field of environmental engineering. Sludge-based biochar (SBB) prepared from ES was used to recover uranium from UCW. Excellent effects were achieved when SBB was modified by acetic acid. Compared with SBB, acetic acid modified SBB (ASBB) has shown three characteristics deserving interest: (i) High sorption efficiency, which the sorption ratio of U(VI) was increased by as high as 35.0%; (ii) Fast sorption rate, as the equilibrium could be achieved within 5.0 min; (iii) Satisfied sorption /desorption behavior, as a matter of fact the sorption rate of U(VI) could still be maintained at 93.0% during the test cycles. In addition, based on the test conditions and various characterization results, it emerged a dual effect of acetic acid on the surface of SBB, i.e. to increase the porosity and add (-COOH) groups. It was revealed that U(VI) and -COO- combined in the surface aperture of ASBB via single-dentate coordination. Altogether, a new utilization mode for SBB is here proposed, as a mean for efficient uranium sorption from UCW.